한강수계의 생물학적 감시망 설치를 위한 저서 대형무척추동물의 생태학적 평가 - 이방흔 (연세대학교 보건대학원, 1987)
[한글] 한강수계의 오염상을 생태학적 입장에서 평가하기 위하여 1985년9월부터 1986년3월까지 7개월간 한강수계 16개 지점을 대상으로 저서대형 무척추동물을 정량적으로 채집하고 종의 다양도, 각 지점의 유사도지수, 우점종분석, 오염지표종의 결정등 생태학적 분석을 하 였다. 종의 다양도지수(d^^2)는 남한강 상류인 안미천에서 3.75로 최고값을 나타냈으며 중량천에서 0.00으로 최저값을 보였다. 대체로 의암댐 부근 강촌, 하안미천, 상안미천, 충북하영천, 봉황천등에서 d^^2≥3을 나타내어 비오염지역으로 판정되었으며, 서울지역 각 지천지점에서는 d^^2 값이 0.14이하 이어서 심한 오염수역임을 알 수 있었다. 각 지점간의 유사도지수 비교치의 최고값은 탄천과 안양천 두 지점간이었으며(C = 0.88) 최저값은 여주지천과 남한산성 주위의 상옥천이었다(C = 0.06). 전반적으로 하류로 내려갈수록 지역간의 유사도지수가 커짐을 알 수 있었다. 이는 한강하류 지점들이 과거의 pollutional stress로 종의 다양도(d^^2)는 크게 줄고 오염에 잘 견디는 Oligochaedae를 주종으로 수개종만이 번성하고 있음에 그 원인이 있다고 볼 수 있다. 한강상류지역의 우점종은 춘천지역 수계에서는 Chironomus spp.이었으며 남한강 상류지역이 Tipula sp.TA 및 Ephemera orientalis Potamanthus nb, Ephemerella rufa, Epeorus latifolium이었고 한강 하류는(특히 천호대교 이하) Ligochaedae를 주종으로한 4∼5종에 불과했다. 이들 자료와 이화학적 수질검사 항목간의 상관성 분석결과 종의 다양도와 상관성이 높은 항목은 D 0 (dissolved oxygen)이었고 다음은 S S(suspended solids)로 나타났다. 이상의 결과를 종합해 보면 한강하류로 내려갈수록 종의 다양도는 낮아지고 지점간의 유사도지수는 높아지며, 하류로 갈수록 Oligochaedae, Chironomus spp.등의 오염지표종이 주류를 이루고 있는 것으로 밝혀졌고, 종의 다양도지수 및 출현종수와 상관성이 가장 큰 항목은 용존산소량이었다. [영문] In ecological assay of the community structures of benthic macroinvertebrates in the Han river system was carried out from September 1985 through March 1986. The benthos was quantitatively collected using Surber sampler, Ponar and Eckman grabs from 16 stations along Han river system, and water specimens were also periodically sampled firm each station for chemical analyses. Species diversity indices(d^^2), similarity coefficients(c), dominant indices(DI) and indicator species were mainly calculated or determined with the macroinvertebrate specimens collected from each station, and multiple regression analysis was employed to determine which chemical factors are affecting the community structures. The a result obtained in this study are summarized as follows: 1. As a result of d^^2 analyses, the upper and twiddle regions of Han river were regarded as unpolluted and healthy(d^^2>3.00), and the station at down stream as severely polluted(d^^2 = 0-0.14). 2. Low similarities between the upper and down regions were shown (c = 0.06 - 0.34), while the stations at down stream showed relatively high similarities each other (c = 0.60 - 0.88). 3. Ephemera orientalis, Potamanthus spp, Ephemerella rufa, Epeorus latifolium were dominant in the upper and middle reginos of Han river, and Oligochaedae and Simulium decorum weirs regared as dominant species in down streams. 4. Limnodrilus gotoi(Oligochaedae) known as tolerant species, was only found in the down streams below Tan-chun area. 5. Dissolved oxygen and suspended solids in water bodies were closely related to affect the density and species diversity of the macroinvertebrate communities. Summarizing the above results, it is fully understandable that the biological monitoring in water systems is as valuable as chemical analyses of water specimens.
환경관리학과/석사